Магнітні хіральні солітони в тонкоплівковому наноконтакті з електричним струмом, стабілізовані полем Ерстеда - Zaspel, C. E.; Wysin, G. M.; Ivanov, B. A. (Publishing house "Academperiodika", 2019)
Static magnetic solitons in a thin film such as skyrmions are metastable states that can be stabilized through a balance of the exchange interaction and various relativistic interactions. One of the most effective stabilizing terms is the antisymmetric exchange along with others such as magnetostatic interactions in confined structures, as well as a current-carrying nanocontact on a thin ferromagnetic film. In this article, the effect of a nanocontact current on the energies of both topological (T-type) and nontopological (NT-type) solitons has been investigated. Without an antisymmetric exchange interaction, the Oersted field from a nanocontact can stabilize both soliton types with the NT soliton as the ground state. With the antisymmetric exchange, there is a critical nanocontact current, where the T soliton becomes the ground state.